A zebrafish model for FHL1-opathy reveals loss-of-function effects of human FHL1 mutations - Keßler, Mirjam; Fuchs, Alexander Sebastian; Kayvanpour, Elham; Katus, Hugo; Schoser, Benedikt; Scheßl, Joachim; Just, Steffen; Rottbauer, Wolfgang (Neuromuscular disorders, 2018)
Missense mutations in the four and a half LIM domain 1 (FHL1) gene were found to cause X-linked inherited myopathies of both skeletal and heart muscles. However, the mechanisms by which FHL1 mutations impact on FHL1 function and lead to alteration of muscle structure and function have not been deciphered yet. We generated here by Morpholino-modified antisense oligonucleotide-mediated gene knockdown fHL1-deficient zebrafish embryos. Similar to the human situation, fhl1a-morphants zebrafish displayed severe skeletal and heart muscle myopathy. Whereas ectopic expression of wild-type FHL1 (FHL1 wt) suppressed both skeletal and heart muscle myopathy in fhl1a-morphants zebrafish, overexpression of the FHL1-opathy associated human mutations FHL1-H123Y, FHL1-C132F or FHL1-C224W did not rescue skeletal and heart muscle myopathy in fhl1a-morphants. Overexpression of FHL1-H123Y, FHL1-C132F or FHL1-C224W in wild-type zebrafish did not induce myopathy in a dominant-negative mode. Altogether these results indicate that FHL1 mutations found to cause X-linked FHL1-opathies in humans consistently lead to severely impaired FHL1 function.
Gesehen am 23.10.2019